A critical analysis of Building Information Modelling systems used in construction projects. (December 2015) - Abanda, F.H.; Vidalakis, C.; Oti, A.H.; Tah, J.H.M.
Highlights: Construction life cycle project needs to be understood for BIM to be easily integrated. Interoperability is crucial for the uptake of BIM in the construction industry. Supply chain members need to collaborate on projects to deliver BIM compliant projects. There is a need for vendors/manufacturers to adopt a common language in publishing information about BIM software. Abstract: Building Information Modelling (BIM) is now a global digital technology which is widely believed to have the potential to revolutionise the construction industry. This has been mainly a result of worldwide government initiatives promoting BIM uptake to improve efficiency and quality in delivering construction projects. This push has been accompanied by the release of a tremendous amount of BIM software systems which are now available in the market. Although this can be seen as a positive development, one cannot ignore how it has overwhelmed many professionals who cannot easily distinguish between the uses of these software systems. Previous studies about different BIM systems have generally been limited in scope focusing predominantly on operational issues. This study aims to conduct a comprehensive and critical appraisal of a wide range of BIM software systems currently being used in managing construction project information. To achieve this, five main methods are adopted. These include a systematic review of the literature, a structured questionnaire survey, action learning, focus group discussions and email surveys. It has to be noted that, although it is impossible to examine the totality of BIM systems, the study adopts a holistic approach looking at most of the major BIM system categories and 122 application examples which are common in the architecture, engineering and construction (AEC) industry.